Built-in self-test techniques for analog and mixed signal circuits - Zakizadeh, Jila (University of Ottawa (Canada), 2005)
The present thesis attempts to develop new techniques for testing analog parts of embedded cores-based mixed signal integrated circuits and systems. In particular, the oscillation based test methodologies have been investigated in the thesis. In the oscillation based test methods, the circuit under test (CUT) is first converted to an oscillator in the test mode and the oscillation parameters, viz. frequency, amplitude, etc. are then measured. Any deviation of these parameters causes either the oscillation frequency of the converted CUT to differ from its nominal value, or the converted CUT stops oscillation altogether. For evaluation purpose, a program has been written in C to help us in simulating our test methodologies. The program is used to inject faults to the circuit under test. The detailed experimental results provided give frequency and amplitude measurements data performed on the individual circuit blocks together with fault coverage. In this work, however, only catastrophic faults were considered. The simulation experiments carried out on different circuits not only demonstrate that the developed approaches are quite feasible but show in addition that the fault coverage is quite satisfactory (100%) in all cases.
Keywords: Engineering, System Science.